Pengaruh investasi teknologi informasi terhadap kinerja perusahaan - Ludipa, Olin Meisa; Rahayu, Rita; Juita, Verni (Jurnal Kajian Manajemen Bisnis, 2018)
The purpose of this study is to determine whether information technology affects firm performance. This type of research is causal-comparative. The population in this study are all companies listed in Indonesian securities. Where the sample is selected by using matched sample comparison group method, obtained 22 companies winning IT award and 22 control firm. Data collection method is documentation method. The analytical method used is non-parametric variation Mann-Whitney Test. The results of this study found that information technology does not affect the firm performance.Keywords: Kinerja Perusahaan; Investasi Teknologi; Informasi; TI; efisiensi.